Gene expression profile of ADAMs and ADAMTSs metalloproteinases in normal and malignant plasma cells and in the bone marrow environment - Bret, Caroline; Hose, Dirk; Reme, Thierry; Kassambara, Alboukadel; Seckinger, Anja; Meißner, Tobias; Schved, Jean-François; Kanouni, Tarik; Goldschmidt, Hartmut; Klein, Bernard (Experimental hematology, 2011)
Objective - The ADAM (a disintegrin and metalloproteinases) and the related ADAMTS (a disintegrin and metalloproteinases with thrombospondin) motifs metalloproteinases are membrane-anchored and secreted proteins exhibiting key roles in mediating cell adhesion, proteolytic shedding, and cell signaling. Dysregulation of these proteins has been observed in some pathologic states, including cancers. Their contribution to multiple myeloma, a plasma-cell neoplasia strongly dependent on bone marrow environment, has been poorly characterized. - Materials and Methods - We analyzed the expression of genes encoding for these proteins and their inhibitors (tissue inhibitor of metalloproteinases [TIMP], reversion-inducing cysteine-rich protein with kazal motifs) in normal B-cell differentiation, primary malignant plasma cells, human myeloma cell lines, and various bone marrow environment cells. The prognostic value of the expression of these genes was analyzed in two independent series of newly diagnosed patients. - Results - ADAM28 and ADAMTS6 were overexpressed in normal memory B cells, ADAM10 and ADAM19 in plasmablasts, and TIMP1 and TIMP2 in normal bone marrow plasma cells. ADAMTS9 was aberrantly expressed by primary malignant plasma cells and ADAM23 expression was associated with a bad prognosis, its expression being spiked in some primary myeloma cell samples. Bone marrow environment cells displayed distinct expression profiles for genes encoding for ADAMs and their inhibitors. They expressed ADAMTSs genes at a low level, with the exception of bone marrow stromal cells. - Conclusions - This study provides an overview of expression data related to ADAMs and ADAMTSs genes potentially involved in myeloma pathogenesis.